Interview with Binod Bihari Chowdhury of Chittagong Armory Raid (1930) on the Anti British Liberation Struggle of India. Interviewed in Dhaka, 07/12/2007 - Kabir, Shahriar.
Interview with Binod Bihari Chowdhury of Chittagong Armory Raid (1930) on the Anti British Liberation Struggle of India. Interviewed in Dhaka, 07/12/2007.